Effect of raffinose and ultrasound pulses on invertase release by free and immobilized Saccharomyces cerevisiae in loofa (Luffa cylindrica) sponge - Leila Larisa Medeiros Marques; João Batista Buzato; Maria Antonia Pedrine Colabone Celligoi (Brazilian Archives of Biology and Technology, 2006)
This study investigated the effect of raffinose and ultrasound pulses on invertase release from free S. cerevisiae and S. cerevisiae immobilized in Luffa cylindrica. The free cell culture was submitted to 2% raffinose pulse and irradiated for 2 minutes at 0.12 and 0.46 h-1 dilution rates. The immobilized cell culture was submitted to raffinose pulse and irradiated for 1, 2 and 4 minutes, at 0.10 h-1 dilution rate. In immobilized cells, the raffinose pulse increased the invertase activity from 5.38 to 7.27 U/mg. Ultrasound application in free cell culture at the 0.12 h-1 dilution rate gave the best results. The activity varied from 25.08 to 29.38 U/mg while the increase in immobilized cells was from 5.22 to 9.70 U/mg when sonicated for two minutes. These results showed that ultrasound application in continuous culture could have great potential for application in biotechnological techniques. Neste trabalho investigou-se o efeito de pulsos de rafinose e ultra-som, na liberação de invertase de Saccharomyces cerevisiae livre e imobilizado em Luffa cylindrica. A cultura de células livres foi submetida a pulso de rafinose 2% e irradiada por 2 min, nas taxas de diluição 0,12 e 0,46 h-1. A cultura de células imobilizadas foi submetida a pulso de rafinose e irradiada por 1, 2 e 4 min, em taxa de diluição 0,10 h-1. Em células imobilizadas, o pulso de rafinose aumentou a atividade invertásica de 5,38 para 7,27 U/mg. Entretanto a aplicação do ultra-som, em cultivo de células livres na taxa de diluição 0,12 h-1, obteve-se os melhores resultados. A atividade variou de 25,08 para 29,38 U/mg, enquanto que o aumento em células imobilizadas foi de 5,22 para 9,70 U/mg, quando sonicadas por 2 min. Esses resultados demonstram que a aplicação de ultra-som, em cultivo contínuo de células livres, pode ter um grande potencial de aplicação em processos biotecnológicos.